ROLE OF NON-FORMAL EDUCATION IN PROMOTING GIRL–CHILD EDUCATION IN NIGERIA - ABDULLAHI, AMINA SHEHU; SHEHU, MARYAM IBRAHIM (Sokoto Educational Review, 2023)
Girl child education is highly valued not only in Nigeria but across the globe. Statistically, the majority of illiterates worldwide are women, and this trend is also prevalent in northern Nigeria, where 65% of enrolled children are boys, leaving a significant number of girls out of school. This paper delves into the factors influencing girls’ education in northern Nigeria, as well as the societal benefits of educating girls. It reviews international literature on this topic and applies it to the situation in northern Nigeria. The study concludes that despite efforts made by various governments, including Nigeria’s, to ensure sufficient educational opportunities for all, a noticeable gap persists. Additionally, in the North, this situation notably impacts generational upbringing and moral training. In response to these challenges, seven recommendations are proposed for a collaborative effort between the formal and non-formal sectors to eradicate illiteracy in our society.